RESPON PERTUMBUHAN TANAMAN SENGON (PARASERIANTHES FALCATARIA) TERHADAP PEMBERIAN AMELIORAN PADA MEDIA CAMPURAN TANAH PASCATAMBANG BATU KAPUR - Alawiyah Alawiyah; Slamet Budi Yuwono; Melya Riniarti; Dermiyati Dermiyati; Christine Wulandari (Lambung Mangkurat University-Indonesia, 2021)
Open mining activities have caused soil damage, water pollution, air pollution, and damage to vegetation. Limestone post mining is a critical area that must be rehabilitated to be productive again. This problems can be fixed by doing land reclamation activities which mandated in the Mining Law Number 4, 2009. The success of land reclamation is largely determined by the choice of plant species and the provision of appropriate soil enhancers (ameliorant). This study was aimed to analyze the growth response of sengon plants on giving ameliorant in mixed limestone post mining soil. This study was designed in completely randomized design for 7 treatments and 3 replications used combination of ameliorant: P0 (without ameliorant); P1 (AH 4 kg ha-1); P2 (BFA 350 kg ha-1); P3 (FMA 500 spores plant-1); P4 (the combination of AH and FMA); P5 (the combination of BFA and FMA); and P6 (the combination of AH, BFA, and FMA). Data were processed by analysis of variance at the 0,05 significance level followed by the Least Significant Difference test. The results showed that the best growth response of sengon on giving ameliorant in mixed limestone post mining soil was P1 treatment (humic acid material) which significantly increased root length, root volume, root fresh weight, shoot fresh weight, root dry weight, and shoot dry weight in sengon plants. The addition of ameliorant can be recommended to improve the quality of revegetation plants